The effects of group set-up on participation and learning in discussion forums. Issue 5 (26th July 2021) - Schenker, Theresa
Abstract: The present study investigated the effects of group set-up in a semester-long telecollaborative discussion forum project in second-semester German. In order to explore whether group set-up affects learning in discussion forums, small groups of non-native speakers (NNS) of German were partnered either with native speakers (NS), other NNS with the same L1, or other NNS with different L1s. The study compared participation and negotiation of meaning routines between the three groups, and assessed overall writing development of the second-semester German learners as a result of forum participation. Data were analyzed using descriptive statistics as well as an analysis of the negotiation of meaning episodes (Varonis & Gass, 1985 ) to reveal whether any of the three groups offers a more productive language learning environment. Results indicate that the NS–NNS groups participated the most in the forum and produced the highest amount of negotiation of meaning routines. Students reached higher writing proficiency than comparable second-semester students who did not complete a discussion forum task.